Prevalence of OCT1 (rs628031) genetic polymorphism in south Indian population - Swathi Swaroopa Borra, Bhavya Chebrolu, Poojitha Thotakura, Sujin Bright Francis Joice, Vasanth Raj Palanimuthu, Sadagoban Gopal Krishnamoorthy, Arun Kanniyappan Parthasarathy (Journal of Applied Pharmaceutical Science, 2021)
Genetic polymorphism is defined as the presence of a heterozygous deoxyribose nucleic acid (DNA) variant in greater than 1% of the population. Genetic polymorphism integrates genetic information in clinical decision-making. High polymorphism of organic cation transporters (OCT) transport genes may represent a significant portion of the variation in the pharmacokinetics and pharmacodynamics of substrate drugs transported by OCT1. The scarcity of research and the difference of effect in the genetic variability of the rs628031 polymorphism in various groups provide compelling reasons to perform the study. The purpose of this study is to find the prevalence of rs628031 polymorphism in the South Indian population. The phenol-chloroform technique was used to extract DNA from 48 healthy individuals in the research. Polymerase chain reaction was used to amplify the acquired DNA samples. After digestion with a tailored restriction enzyme, restriction fragment length polymorphism was utilized to discover genetic polymorphisms. The minor allele frequency of rs628031 was 0.67, indicating its deviation with the Hardy–Weinberg principle. The frequency of variant alleles discovered in this study was comparable to that seen in the Javanese population. The study's major findings provide the groundwork for future pharmacogenetic investigations in this group, as well as contribute to a better understanding of the role of the rs628031 polymorphism in drug response and benefit in developing a customized treatment regimen with improved efficacy and safety.
Keywords: OCT1, rs628031, genetic polymorphism, SLC22A1, SNP.